Heterogeneous Fenton catalytic material as well as preparation method and application thereof

By generating a covalent organic framework on the surface of single-wall carbon nanotube composite perovskite powder and grafting it on the polyurethane-fluorinated acrylic interpenetrating resin, the ozone oxidation corrosion problem is solved, the life of the catalytic material is extended and the catalytic activity is improved. Dispersibility enables efficient removal of pollutants in black and odorous water bodies.

CN119303628AActive Publication Date: 2025-01-14ANHUI HENGYU ENVIRONMENTAL PROTECTION EQUIPMENT MANUFACTURING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411855262.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-14
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

When existing heterogeneous Fenton catalytic materials cooperate with ozone micro-nano bubble technology to treat black and odorous water bodies, ozone has an oxidative corrosion effect on the resin, resulting in a shortening of the service life of the catalytic material.

Method used

By orderly filling Fe3+ perovskites into the lumen of single-wall carbon nanotubes, and forming a Fe3+-loaded covalent organic skeleton on the surface of the carbon nanotube composite perovskite powder, the efficient catalytic material is grafted on the polyurethane -Fluorinated acrylic interpenetrating resin forms a stable heterogeneous Fenton catalytic material to avoid ozone oxidation and corrosion.

Benefits of technology

It extends the service life of catalytic materials, improves catalytic activity and dispersion, enhances the utilization rate of iron ions, reduces the generation of iron sludge, and improves the removal efficiency of conventional pollutants and toxic micropollutants in polluted water bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a heterogeneous Fenton catalytic material and a preparation method and application thereof, and belongs to the technical field of heterogeneous Fenton catalytic materials.The preparation method comprises the steps that perovskite with catalytic activity and Fe < 3 + > at the B site is prepared, a tube cavity of a single-walled carbon nanotube is sequentially filled with the perovskite, and stable carbon nanotube composite perovskite powder is obtained; the carbon nano tube composite perovskite powder has efficient and stable catalytic activity, a Fe < 3 + >-loaded covalent organic framework is generated on the surface of the carbon nano tube composite perovskite powder in situ, the dispersity of the carbon nano tube composite perovskite powder is improved, an efficient catalytic material is grafted to polyurethane-fluorinated acrylic acid interpenetrating resin, and the heterogeneous Fenton catalytic material is obtained. In the application of coupling ozone micro-nano bubbles to treat black and odorous water, as a nucleation point of the micro-nano bubbles, formation and dispersion of the bubbles are promoted, and the mass transfer efficiency is improved; in addition, the oxidation and corrosion effects of ozone on the heterogeneous Fenton catalytic material are effectively avoided, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heterogeneous Fenton catalytic materials, and specifically relates to a heterogeneous Fenton catalytic material and a preparation method and application thereof. Background Art

[0002] In recent years, remarkable results have been achieved in water pollution prevention and control. The water quality of the main river basins is good, but there are still problems such as the water quality of some tributaries and serious pollution in rural rivers. Therefore, the development of efficient and low-carbon in-situ treatment technology for polluted river water is of great significance to protecting the health of the water environment and ensuring regional water safety.

[0003] Heterogeneous Fenton catalytic materials can efficiently degrade organic matter in water bodies. The hydroxyl radicals produced by the Fenton reaction are highly oxidizing and can attack the chemical bonds in organic molecules. They are widely used in the pretreatment of heavily polluted wastewater and deep treatment of drinking water. Ozone micro-nano bubble technology can efficiently remove organic matter, ammonia nitrogen, heavy metals, antibiotics and other pollutants in sewage, improve sewage treatment efficiency and effluent quality, and synergistically enhance the functions of native organisms and improve deep removal efficiency through micro-nano bubbles, thereby achieving low-cost and efficient removal of conventional pollutants and toxic micro-pollutants in polluted water bodies.

[0004] Most of the heterogeneous Fenton catalytic materials in the existing technology are based on resin. When used in conjunction with ozone micro-nano bubble technology to treat black and odorous water bodies, ozone has an oxidative corrosive effect on the resin, thereby reducing the service life of the catalytic material. Summary of the invention

[0005] The present invention aims to prepare a heterogeneous Fenton catalytic material by replacing Fe 3+ The perovskite is orderly filled into the lumen of the single-walled carbon nanotube to obtain a stable carbon nanotube composite perovskite powder, and the loaded Fe is in situ generated on the surface of the carbon nanotube composite perovskite powder. 3+ The covalent organic skeleton is used to graft the high-efficiency catalytic material onto the polyurethane-fluorinated acrylic interpenetrating resin. In the application of coupling ozone micro-nano bubbles to treat black and odorous water bodies, the oxidation and corrosion of ozone on the heterogeneous Fenton catalytic material can be effectively avoided, thereby extending the service life.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A heterogeneous Fenton catalytic material is prepared by the following steps: Step 1: Add citric acid and 50-60% ethylenediaminetetraacetic acid solution into a reactor, add ammonia water dropwise until the mixed solution is clear, stir for 30-40 minutes at 20-25°C and 500-600r / min, add lanthanum nitrate hexahydrate, ferric chloride hexahydrate, ferric nitrate and deionized water into the reactor, stir for 1-2 hours at 75-80°C and 500-600r / min, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, vacuum dry at 120-140°C for 3-4 hours, grind, place the obtained powder in a muffle furnace, keep warm at 950-1000°C under nitrogen protection for 2-4 hours, cool naturally, and obtain perovskite powder.

[0007] Step 2: Add single-walled carbon nanotubes with a diameter of 1-2 nm and a length of 1-1.2 μm and a nitric acid solution with a concentration of 1 mol / L into a reactor, perform acid washing for 1-1.2 h at 20-25° C. and 400-500 r / min, filter, and wash the filter cake with deionized water until the last washing liquid is neutral to obtain modified single-walled carbon nanotubes; place the modified single-walled carbon nanotubes and perovskite powder in a silicon dioxide reactor, seal under vacuum, stir for 48-50 h at 550-600° C. and 400-500 r / min, centrifuge and filter at 2000-2500 r / min, wash the filter cake with anhydrous ethanol 2-3 times to obtain carbon nanotube composite perovskite powder.

[0008] Step 3: Add carbon nanotube composite perovskite powder, 2,3-dihydroxyterephthalaldehyde and deionized water into a reactor, stir for 40-45 minutes at 20-25°C and 500-700r / min, add 1,3,5-tri(4-aminophenyl)benzene into the reactor, stir for 10-12 minutes at 20-25°C and 500-700r / min, then add dimethylacetamide, N,N-dimethylformamide and 4-5mol / L acetic acid solution into the reactor, continue stirring for 1-2h, then add ferric chloride hexahydrate into the reactor, continue stirring for 1-2h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry at 60-80°C for 1-2h to obtain a high-efficiency catalytic material.

[0009] Step 4: Add high-efficiency catalytic material, perfluoroethyl octyl acrylate and deionized water into the reactor, stir for 40-45 minutes at 20-25°C and 500-700r / min to obtain a precursor solution; add polyether polyol, acrylic acid solution with a neutralization degree of 65-70% and deionized water into the reactor, stir for 40-45 minutes at 20-25°C and 500-700r / min, add isocyanate and dibutyltin dilaurate solution with a mass fraction of 0.3-0.5% into the reactor, stir at 70-80°C and 500-600r / min. / min, stir and react for 20-30 minutes, then add the precursor solution into the reactor, introduce nitrogen protection, stir and react for 1-2 hours at 95-100°C and 500-600r / min, cool to 55-65°C, add sodium sulfite as an initiator and hydroxymethyl acrylamide as a cross-linking agent into the reactor, heat to 70-80°C, stir at 500-600r / min for 3-4 hours, filter, wash the filter cake with ionized water and anhydrous ethanol for 2-3 times respectively, and dry in vacuo at 60-80°C for 1-2 hours to obtain a heterogeneous Fenton catalytic material.

[0010] Furthermore, in step 1, the dosage ratio of citric acid, ethylenediaminetetraacetic acid, lanthanum nitrate hexahydrate, ferric chloride hexahydrate, ferric nitrate and deionized water is 8-9g:500-600mL:9-10g:9-10g:8-9g:400-500mL.

[0011] Furthermore, in step 2, the dosage ratio of single-walled carbon nanotubes to nitric acid is 2-3 g: 200-300 mL.

[0012] Furthermore, in step 2, the mass ratio of the modified single-walled carbon nanotubes to the perovskite powder is 1:2.

[0013] Furthermore, in step three, the usage ratio of carbon nanotube composite perovskite powder, 2,3-dihydroxyterephthalaldehyde, deionized water, 1,3,5-tri(4-aminophenyl)benzene, dimethylacetamide, N,N-dimethylformamide, acetic acid and ferric chloride hexahydrate is 5-6g:4-5g:200-300mL:5-6g:100-200mL:100-200mL:80-90mL:3-4g.

[0014] Furthermore, in step 4, the usage ratio of the high-efficiency catalytic material, perfluoroethyl octyl acrylate and deionized water is 2-3 g: 50-70 mL: 200-300 mL.

[0015] Furthermore, in step 4, the usage ratio of polyether polyol, acrylic acid, deionized water, isocyanate, dibutyltin dilaurate, precursor solution, sodium sulfite and hydroxymethyl acrylamide is 80-100 mL: 50-70 mL: 200-300 mL: 50-70 mL: 20-30 mL: 200-300 mL: 0.5-0.7 g: 0.5-0.7 g.

[0016] The present invention also provides an application of a heterogeneous Fenton catalytic material coupled with ozone micro-nano bubbles to treat black and odorous water bodies.

[0017] Beneficial effects of the present invention: 1. The heterogeneous Fenton catalytic material prepared by the present invention is a single-walled carbon nanotube with a B position of Fe 3+ The perovskite was incorporated into the tube and treated with nitric acid to generate Fe-loaded in situ on the surface of the single-walled carbon nanotubes. 3+ A covalent organic skeleton is formed to obtain a high-efficiency catalytic material, and the high-efficiency catalytic material is grafted onto the surface of the polyurethane-fluorinated acrylic interpenetrating resin through the covalent skeleton to obtain a structurally stable heterogeneous Fenton catalytic material with high-efficiency and stable catalytic activity; the fluorine atoms in the polyurethane-fluorinated acrylic interpenetrating resin have a good shielding and protective effect on the main chain and internal molecules. In the treatment of black and odorous water bodies combined with ozone micro-nano bubble technology, the heterogeneous Fenton catalytic material has a large specific surface area, which can be used as a nucleation point for micro-nano bubbles, promote the formation and dispersion of bubbles, thereby increasing the gas-liquid contact area and improving the mass transfer efficiency; and it can effectively avoid the oxidation and corrosion of ozone on the heterogeneous Fenton catalytic material and extend its service life.

[0018] 2. The carbon nanotube composite perovskite powder of the present invention arranges the perovskite in an orderly manner in the tube cavity through the capillary effect and the interaction force between molecules, and is evenly dispersed in the catalytic material. A covalent skeleton is generated in situ on the surface to obtain a high-efficiency catalytic material. The high-efficiency catalytic material is grafted onto the polyurethane-fluorinated acrylic interpenetrating resin, so that the high-efficiency catalytic material can be stably and evenly dispersed on the surface, which helps to improve the dispersibility of the carbon nanotube composite perovskite powder; and the Fe-loaded 3+ The covalent organic skeleton is grafted onto the resin, which further realizes the effective utilization of iron ions and prevents the iron ions from falling off the surface of the catalyst material and entering the solution, resulting in the loss of iron ions, thereby reducing the generation of iron sludge and improving the utilization rate of the catalyst material. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1: A heterogeneous Fenton catalytic material is prepared by the following steps: S1: Add 40g of citric acid and 2.5L of 50% ethylenediaminetetraacetic acid solution into a reactor, add ammonia water dropwise until the solution is clear, stir for 30min at 20°C and 500r / min, add 45g of lanthanum nitrate hexahydrate, 45g of ferric chloride hexahydrate, 40g of ferric nitrate and 2L of deionized water into the reactor, stir for 1h at 75°C and 500r / min, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, dry it in vacuum at 120°C for 3h, grind, place the obtained powder in a muffle furnace, keep it warm at 950°C for 2h under nitrogen protection, cool naturally, and obtain perovskite powder.

[0021] Perovskite is a compound with an ABO3 structure. It is produced by using lanthanum nitrate hexahydrate, ferric chloride hexahydrate and ferric nitrate as monomers. 3+ , B position is Fe 3+ A stable structure with catalytic activity; citric acid can form complexes with metal ions, which helps to evenly disperse the metal ions in the solution. This dispersion effect can prevent the agglomeration and precipitation of perovskite particles, thereby improving the stability and uniformity of perovskite. Calcination in a muffle furnace can remove moisture, organic matter and other volatile impurities in the perovskite precursor, ensuring the purity and quality of the perovskite.

[0022] S2: 2 g of single-walled carbon nanotubes with a diameter of 1 nm and a length of 1 μm and 200 mL of 1 mol / L nitric acid solution were added to a reactor, acid-washed at 20°C and 400 r / min for 1 h, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral to obtain modified single-walled carbon nanotubes; 2 g of modified single-walled carbon nanotubes and 4 g of perovskite powder were placed in a silica reactor, sealed under vacuum, stirred at 550°C and 400 r / min for 48 h, centrifuged at 2000 r / min, and the filter cake was washed twice with anhydrous ethanol to obtain carbon nanotube composite perovskite powder.

[0023] Single-walled carbon nanotubes are soaked in nitric acid to remove impurities on the surface. The nitrate ions and hydrogen ions in the nitric acid will attack the unsaturated carbon atoms on the surface of the carbon nanotubes. The unsaturated carbon atoms are oxidized and form carboxyl groups in their place. The two ends of the single-walled carbon nanotubes are closed shapes composed of carbon five-membered rings and seven-membered rings, which have poor stability. In an air atmosphere, when heated to 550°C, the two ends of the single-walled carbon nanotubes will react with oxygen, causing the two ends to untie, thereby achieving the goal of wrapping the perovskite inside the single-walled carbon nanotubes.

[0024] By utilizing the capillary effect and intermolecular interaction forces of the single-walled carbon nanotube lumen, the perovskite material can be arranged in an orderly manner along the lumen direction. The surface of the carbon nanotube has a high surface energy, which makes it difficult for foreign substances to adsorb and disperse on its surface. In contrast, the interior of the lumen is easier to achieve stable filling of foreign substances due to space limitations and the balance of intermolecular interaction forces.

[0025] S3: 5g of carbon nanotube composite perovskite powder, 4g of 2,3-dihydroxyterephthalaldehyde and 200mL of deionized water were added to the reactor, stirred at 20°C and 500r / min for 40min, 1g of 1,3,5-tri(4-aminophenyl)benzene was added to the reactor, stirred at 20°C and 500r / min for 10min, 100mL of dimethylacetamide, 100mL of N,N-dimethylformamide and 80mL of 4mol / L acetic acid solution were added to the reactor, and stirring was continued for 1h, 5g of ferric chloride hexahydrate was added to the reactor, and stirring was continued for 1h, filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol respectively, and dried under vacuum at 60°C for 1h to obtain a high-efficiency catalytic material.

[0026] After the single-walled carbon nanotubes were treated with nitric acid, a large number of carboxyl groups on the surface reacted with the hydroxyl groups of 2,3-dihydroxyterephthalaldehyde to generate Fe-loaded Fe on the surface of the carbon nanotube composite perovskite powder. 3+ The covalent organic framework is used to bind Fe 3+ Fixed, increase Fe 3+ The utilization rate of the material is large, and it has a large specific surface area and porous properties, which can increase the active sites.

[0027] S4: 2g of high-efficiency catalytic material, 50mL of perfluoroethyl octyl acrylate and 200mL of deionized water were added to the reactor, and stirred at 20℃ and 500r / min for 40min to obtain a precursor solution; 80mL of polyether polyol, 50mL of acrylic acid solution with a neutralization degree of 65% and 200mL of deionized water were added to the reactor, and stirred at 20℃ and 500r / min for 40min; 50mL of isocyanate and 20mL of dibutyltin dilaurate solution with a mass fraction of 0.3% were added to the reactor, and the mixture was stirred at 20℃ and 500r / min for 40min. The reaction was stirred at 70°C and 500 r / min for 20 min, and then 200 mL of the precursor solution was added to the reactor. Nitrogen was introduced for protection. The reaction was stirred at 95°C and 500 r / min for 1 h. The reaction was cooled to 55°C, and 0.5 g of sodium sulfite as an initiator and 0.5 g of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor. The reaction was heated to 70°C and stirred at 500 r / min for 3 h. The reaction was filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol respectively, and dried in vacuo at 60°C for 1 h to obtain a heterogeneous Fenton catalytic material.

[0028] The highly efficient catalytic material with active hydroxyl functional groups reacts with perfluoroethyl octyl acrylate in an aqueous solution to obtain a precursor solution. The polyether polyol molecular formula contains multiple hydroxyl sites that can react with acrylic acid and combine with the isocyanate in the isocyanate under the action of the catalytic material. Finally, under the action of an initiator and a cross-linking agent, it polymerizes with the precursor solution to obtain a porous heterogeneous Fenton catalytic material, the surface of which is grafted with a polyurethane-fluorinated acrylic interpenetrating resin of the highly efficient catalytic material.

[0029] Example 2: A heterogeneous Fenton catalytic material is prepared by the following steps: S1: Add 42.5g of citric acid and 2.75L of 55% ethylenediaminetetraacetic acid solution into a reactor, add ammonia water dropwise until the solution is clear, stir for 35min at 23°C and 550r / min, add 47.5g of lanthanum nitrate hexahydrate, 47.5g of ferric chloride hexahydrate, 42.5g of ferric nitrate and 2.25L of deionized water into the reactor, stir for 1.5h at 78°C and 550r / min, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, dry it in vacuum at 130°C for 3.5h, grind, place the obtained powder in a muffle furnace, keep it warm at 980°C for 3h under nitrogen protection, cool naturally, and obtain perovskite powder.

[0030] S2: 2.5 g of single-walled carbon nanotubes with a diameter of 1.5 nm and a length of 1.1 μm and 250 mL of 1 mol / L nitric acid solution were added to a reactor, acid-washed for 1.1 h at 23°C and 450 r / min, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral to obtain modified single-walled carbon nanotubes; 2.5 g of modified single-walled carbon nanotubes and 5 g of perovskite powder were placed in a silica reactor, sealed under vacuum, stirred at 580°C and 450 r / min for 49 h, centrifuged at 2300 r / min, and the filter cake was washed 3 times with anhydrous ethanol to obtain carbon nanotube composite perovskite powder.

[0031] S3: 5.5g of carbon nanotube composite perovskite powder, 1.5g of 2,3-dihydroxyterephthalaldehyde and 250mL of deionized water were added to the reactor, stirred at 23°C and 600r / min for 43min, 4.5g of 1,3,5-tri(4-aminophenyl)benzene was added to the reactor, stirred at 23°C and 600r / min for 11min, 150mL of dimethylacetamide, 150mL of N,N-dimethylformamide and 85mL of 4.5mol / L acetic acid solution were added to the reactor, and stirring was continued for 1.5h, 5.5g of ferric chloride hexahydrate was added to the reactor, and stirring was continued for 1.5h, filtered, and the filter cake was washed 3 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 70°C for 1.5h to obtain a high-efficiency catalytic material.

[0032] S4: 2.5 g of high-efficiency catalytic material, 60 mL of perfluoroethyl octyl acrylate and 250 mL of deionized water were added to the reactor, and stirred at 23 ° C and 600 r / min for 43 min to obtain a precursor solution; 90 mL of polyether polyol, 60 mL of acrylic acid solution with a neutralization degree of 68% and 250 mL of deionized water were added to the reactor, and stirred at 23 ° C and 600 r / min for 43 min; 60 mL of isocyanate and 25 mL of dibutyltin dilaurate solution with a mass fraction of 0.4% were added to the reactor, and stirred at 75 ℃ and 550r / min, stirring and reacting for 25min, then adding 250mL of precursor solution into the reactor, introducing nitrogen protection, stirring and reacting at 98℃ and 550r / min for 1.5h, cooling to 60℃, adding 0.6g of sodium sulfite as an initiator and 0.6g of hydroxymethyl acrylamide as a cross-linking agent into the reactor, heating to 75℃, stirring at 550r / min for 3.5h, filtering, washing the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and drying in vacuo at 70℃ for 1.5h to obtain a heterogeneous Fenton catalytic material.

[0033] Example 3: A heterogeneous Fenton catalytic material is prepared by the following steps: S1: Add 45g of citric acid and 3L of 60% ethylenediaminetetraacetic acid solution into a reactor, add ammonia water dropwise until the solution is clear, stir for 40min at 25°C and 600r / min, add 50g of lanthanum nitrate hexahydrate, 50g of ferric chloride hexahydrate, 45g of ferric nitrate and 2.5L of deionized water into the reactor, stir for 2h at 80°C and 600r / min, filter, wash the filter cake with deionized water and anhydrous ethanol three times respectively, dry it in vacuum at 140°C for 4h, grind, place the obtained powder in a muffle furnace, keep it warm at 1000°C for 4h under nitrogen protection, cool naturally, and obtain perovskite powder.

[0034] S2: 3 g of single-walled carbon nanotubes with a diameter of 2 nm and a length of 1.2 μm and 300 mL of 1 mol / L nitric acid solution were added to a reactor, acid-washed for 1.2 h at 25°C and 500 r / min, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral to obtain modified single-walled carbon nanotubes; 3 g of modified single-walled carbon nanotubes and 6 g of perovskite powder were placed in a silica reactor, sealed under vacuum, stirred for 50 h at 600°C and 500 r / min, centrifuged at 2500 r / min, and the filter cake was washed 3 times with anhydrous ethanol to obtain carbon nanotube composite perovskite powder.

[0035] S3: 6 g of carbon nanotube composite perovskite powder, 5 g of 2,3-dihydroxyterephthalaldehyde and 300 mL of deionized water were added to the reactor, stirred at 25°C and 700 r / min for 45 min, 2 g of 1,3,5-tri(4-aminophenyl)benzene was added to the reactor, stirred at 25°C and 700 r / min for 12 min, 200 mL of dimethylacetamide, 200 mL of N,N-dimethylformamide and 90 mL of 5 mol / L acetic acid solution were added to the reactor, and stirring was continued for 2 h. 6 g of ferric chloride hexahydrate was added to the reactor, and stirring was continued for 2 h. The reaction was filtered, and the filter cake was washed 3 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 80°C for 2 h to obtain a high-efficiency catalytic material.

[0036] S4: 3g of high-efficiency catalytic material, 70mL of perfluoroethyl octyl acrylate and 300mL of deionized water were added into the reactor, and stirred at 25℃ and 700r / min for 45min to obtain a precursor solution; 100mL of polyether polyol, 70mL of acrylic acid solution with a neutralization degree of 70% and 300mL of deionized water were added into the reactor, and stirred at 25℃ and 700r / min for 45min; 70mL of isocyanate and 30mL of dibutyltin dilaurate solution with a mass fraction of 0.5% were added into the reactor, and the mixture was stirred at 25℃ and 700r / min for 45min. The reaction was stirred at 80°C and 600 r / min for 30 min, and then 300 mL of the precursor solution was added to the reactor. Nitrogen was introduced for protection. The reaction was stirred at 100°C and 600 r / min for 2 h. The reaction was cooled to 65°C, and 0.7 g of sodium sulfite as an initiator and 0.7 g of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor. The reaction was heated to 80°C and stirred at 600 r / min for 4 h. The filter cake was washed three times with deionized water and anhydrous ethanol respectively, and dried in vacuo at 80°C for 2 h to obtain a heterogeneous Fenton catalytic material.

[0037] Comparative Example 1: Based on Example 3, perfluoroethyloctyl acrylate in step S4 was replaced with an acrylic acid solution with a neutralization degree of 70%, and the other steps remained unchanged to prepare a heterogeneous Fenton catalytic material.

[0038] The ozone stability of the heterogeneous Fenton catalytic materials prepared in Examples 1 to 3 and Comparative Example 1 was tested: 2 g of the heterogeneous Fenton catalytic material and 200 mL of deionized water were added to the reactor, ozone micro-nano bubbles were introduced into the reactor at a flow rate of 0.3 L / min, and then 200 mL of H2O2 with a concentration of 1 mg / L was added to the reactor, and the mass of the heterogeneous Fenton catalytic material before and after 90 days of the test of each Example 1-3 and Comparative Example 1 was recorded, thereby evaluating the ozone stability of different heterogeneous Fenton catalytic materials. The ozone stability results of the heterogeneous Fenton catalytic materials are shown in Table 1: Table 1 Ozone stability results of heterogeneous Fenton catalytic materials

[0039] As can be seen from Table 1, the heterogeneous Fenton catalytic materials prepared in Examples 1 to 3 of the present invention have a significantly smaller mass change than that in Comparative Example 1 after 90 days of treatment. The acrylic resin contains structural carbon-carbon double bonds that are easily oxidized, so it is easily oxidized by ozone when combined with ozone micro-nano bubble technology, resulting in corrosion or degradation of the resin, and further corrosion of the catalytic material. The polyurethane-fluorinated acrylic interpenetrating resin of the present invention is an interpenetrating resin formed by polymerizing perfluoroethyloctyl acrylate and acrylic acid as monomers. The fluorine atom in the organic fluorine compound has the smallest atomic radius and the largest electronegativity, which plays a good shielding and protective role on the main chain and internal molecules, and can significantly resist the oxidation and corrosion caused by ozone while maintaining a high degree of stability.

[0040] Comparative Example 2: Based on Example 3, the carbon nanotube composite perovskite powder in step S3 is replaced by the perovskite powder in step S1, and the other steps remain unchanged to prepare a heterogeneous Fenton catalytic material.

[0041] Comparative Example 3: Based on Example 3, the high-efficiency catalytic material in step S4 is replaced by the carbon nanotube composite perovskite powder in step S2, and the other steps remain unchanged to prepare a heterogeneous Fenton catalytic material.

[0042] Comparative Example 4: Based on Example 3, the high-efficiency catalytic material in step S4 is directly used as a heterogeneous Fenton catalytic material.

[0043] In the embodiments and comparative examples: Citric acid, ethylenediaminetetraacetic acid, lanthanum nitrate hexahydrate, ferric chloride hexahydrate, ferric nitrate, 2,3-dihydroxyterephthalaldehyde, 1,3,5-tri(4-aminophenyl)benzene, polyether polyol, isocyanate, sodium sulfite, and hydroxymethyl acrylamide were purchased from Sigma-Aldrich.

[0044] Perfluoroethyloctyl acrylate was purchased from Shandong Lubang Chemical Co., Ltd.

[0045] Single-walled carbon nanotubes were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0046] The ozone generator model is OZ-10G.

[0047] The model of the microbubble generator is SFMB.

[0048] Simulated black and odorous water was purchased from Suzhou Biyuan Environmental Protection Engineering Co., Ltd.

[0049] The performance of the heterogeneous Fenton catalytic materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested: 4g of heterogeneous Fenton catalytic material and 500mL of sewage in simulated black and odorous water bodies were added to the reactor, stirred and dispersed for 10min at 25℃ and 500r / min, the ozone generator was connected to the microbubble generator, the microbubble generator was connected to the bottom of the reactor, and ozone was introduced into the microbubble generator at a flow rate of 0.3L / min from the ozone generator for 30min. After the ozone micro-nano bubbles were formed, they were introduced into the reactor, and then 200mL of H2O2 with a concentration of 1mg / L was added to the reactor. The treatment lasted for 60 days in total, so as to evaluate the effect of each heterogeneous Fenton catalytic material combined with micro-nano bubbles in treating sewage. The specific test method is as follows: 1. According to GB / T11893-1989 "Determination of total phosphorus in water - ammonium molybdate spectrophotometry", the total phosphorus test was performed on the sewage of each embodiment and comparative example before treatment and after treatment for 60 days, and the total phosphorus content (mg / L) was recorded; 2. According to GB / T7479-87 "Nessler's reagent colorimetric method for determination of ammonium in water quality", the sewage of each embodiment and comparative example was tested for ammonia nitrogen before treatment and after treatment for 60 days, and the content of ammonia nitrogen (mg / L) was recorded. The index results of sewage treatment by each heterogeneous Fenton catalytic material combined with micro-nano bubbles are shown in Table 2: Table 2 Index results of various heterogeneous Fenton catalytic materials combined with micro-nano bubbles for treating sewage

[0050] It can be seen from Table 2 that the removal rates of total phosphorus and ammonia nitrogen of the heterogeneous Fenton catalytic materials prepared in Examples 1 to 3 of the present invention are significantly better than those of the comparative examples. In Comparative Example 1, the acrylic resin has good extensibility and adsorption capacity. As a matrix of the catalytic material, it can improve the overall strength of the catalytic material. However, in the application of treating black and odorous water bodies, it is easily oxidized by ozone when combined with ozone micro-nano bubble technology, resulting in corrosion or degradation of the resin, thereby weakening the ability to remove total phosphorus and ammonia nitrogen in black and odorous water bodies.

[0051] In Comparative Example 2, the carbon nanotube composite perovskite powder is replaced with perovskite powder. The perovskite is easy to agglomerate, and the perovskite contains active iron ions, which are easy to fall off from the surface of the perovskite and enter the solution, causing the loss of iron ions. The perovskite is not filled into the pipe of the monomer carbon nanotube, which cannot better protect the structural stability of the perovskite, making the Fe-containing 3+ The perovskite is difficult to stably play a catalytic role, resulting in poor treatment effects of total phosphorus and ammonia nitrogen.

[0052] In Comparative Example 3, the high-efficiency catalytic material was replaced with carbon nanotube composite perovskite powder, and Fe-containing catalyst could not be generated in situ on the surface of the single-arm carbon nanotube. 3+The covalent skeleton of single-arm carbon nanotubes easily forms large bundles and agglomerates. The existence of the nanosize effect makes the agglomeration effect more significant, affecting the catalytic effect of the catalytic material. The covalent skeleton can stably fix the carbon nanotube composite perovskite powder on the polyurethane-fluorinated acrylic interpenetrating resin, which helps to increase the dispersibility of the carbon nanotube composite perovskite powder.

[0053] In Comparative Example 4, the high-efficiency catalytic material is not grafted with the polyurethane-fluorinated acrylic interpenetrating resin. Instead, the high-efficiency catalytic material is directly used as a heterogeneous Fenton catalytic material. The polyurethane-fluorinated acrylic interpenetrating resin can stabilize the structure of the high-efficiency catalytic material, improve the structural strength and toughness of the catalytic material, help increase the dispersibility of the high-efficiency catalytic material, and has a porous nature itself, which can provide more active sites, thereby promoting the catalytic efficiency of the catalytic material.

[0054] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0055] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a heterogeneous Fenton catalytic material, characterized in that: The steps include: Step 1: placing the modified single-walled carbon nanotube and the perovskite powder in a silicon dioxide reactor in a mass ratio of 1:2, vacuum sealing, stirring at 550-600°C and 400-500r / min for 48-50h, centrifugally filtering at 2000-2500r / min, washing the filter cake with anhydrous ethanol 2-3 times, and vacuum drying to obtain carbon nanotube composite perovskite powder; Step 2: Add carbon nanotube composite perovskite powder, 2,3-dihydroxyterephthalaldehyde and deionized water to a reactor, stir at 20-25°C and 500-700r / min for 40-45min, add 1,3,5-tri(4-aminophenyl)benzene to the reactor, stir at 20-25°C and 500-700r / min for 10-12min, add dimethylacetamide, N,N-dimethylformamide and 4-5mol / L acetic acid solution to the reactor, continue stirring for 1-2h, then add ferric chloride hexahydrate to the reactor, continue stirring and reacting for 1-2h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry to obtain a high-efficiency catalytic material; Step 3: Add high-efficiency catalytic material, perfluoroethyl octyl acrylate and deionized water into a reaction kettle, stir at 20-25° C. and 500-700 r / min for 40-45 min to obtain a precursor solution; Add polyether polyol, acrylic acid solution with a neutralization degree of 65-70% and deionized water into a reactor, stir at 20-25°C and 500-700r / min for 40-45min, add isocyanate and 0.3-0.5wt% dibutyltin dilaurate solution, stir at 70-80°C and 500-600r / min for 20-30min, then add the precursor solution into the reactor, introduce nitrogen protection, stir at 95-100°C and 500-600r / min for 1-2h, cool to 55-65°C, add sodium sulfite and hydroxymethyl acrylamide, stir at 70-80°C and 500-600r / min for 3-4h, filter, wash the filter cake with ionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry to obtain a heterogeneous Fenton catalytic material.

2. The method for preparing a heterogeneous Fenton catalytic material according to claim 1, characterized in that: The modified single-walled carbon nanotubes described in step 1 are prepared by the following steps: Single-walled carbon nanotubes with a diameter of 1-2 nm and a length of 1-1.2 μm and a nitric acid solution with a concentration of 1 mol / L are added into a reactor, acid-washed for 1-1.2 h at 20-25° C. and 400-500 r / min of stirring, filtered, and the filter cake is washed with deionized water until the last washing liquid is neutral to obtain modified single-walled carbon nanotubes.

3. The method for preparing a heterogeneous Fenton catalytic material according to claim 2, characterized in that: The usage ratio of the single-walled carbon nanotubes to nitric acid is 2-3 g: 200-300 mL.

4. The method for preparing a heterogeneous Fenton catalytic material according to claim 1, characterized in that: The perovskite powder in step 1 is prepared by the following steps: Add citric acid and 50-60wt% ethylenediaminetetraacetic acid solution into a reaction kettle, add ammonia water dropwise until the mixed solution is clear, stir at 20-25°C and 500-600r / min for 30-40min, then add lanthanum nitrate hexahydrate, ferric chloride hexahydrate, ferric nitrate and deionized water, stir at 75-80°C and 500-600r / min for 1-2h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, vacuum dry at 120-140°C for 3-4h, grind, place the obtained powder in a muffle furnace, protect with nitrogen and keep at 950-1000°C for 2-4h, cool naturally to obtain perovskite powder.

5. The method for preparing a heterogeneous Fenton catalytic material according to claim 4, characterized in that: The dosage ratio of the citric acid, ethylenediaminetetraacetic acid, lanthanum nitrate hexahydrate, ferric chloride hexahydrate, ferric nitrate and deionized water is 8-9g:500-600mL:9-10g:9-10g:8-9g:400-500mL.

6. The method for preparing a heterogeneous Fenton catalytic material according to claim 1, characterized in that: The amount ratio of the carbon nanotube composite perovskite powder, 2,3-dihydroxyterephthalaldehyde, deionized water, 1,3,5-tri(4-aminophenyl)benzene, dimethylacetamide, N,N-dimethylformamide, acetic acid and ferric chloride hexahydrate described in step 2 is 5-6g:4-5g:200-300mL:5-6g:100-200mL:100-200mL:80-90mL:3-4g.

7. The method for preparing a heterogeneous Fenton catalytic material according to claim 1, characterized in that: The usage ratio of the high-efficiency catalytic material, perfluoroethyl octyl acrylate and deionized water in step 3 is 2-3g:50-70mL:200-300mL.

8. The method for preparing a heterogeneous Fenton catalytic material according to claim 1, characterized in that: The usage ratio of the polyether polyol, acrylic acid, deionized water, isocyanate, dibutyltin dilaurate, precursor solution, sodium sulfite and hydroxymethyl acrylamide in step three is 80-100 mL: 50-70 mL: 200-300 mL: 50-70 mL: 20-30 mL: 200-300 mL: 0.5-0.7 g: 0.5-0.7 g.

9. A heterogeneous Fenton catalytic material, characterized in that: The catalyst is prepared by the method for preparing a heterogeneous Fenton catalytic material as described in any one of claims 1 to 8.

10. Use of a heterogeneous Fenton catalytic material according to claim 9 in coupling ozone micro-nano bubbles to treat black and odorous water bodies.

Citation Information

Patent Citations

  • Method for water treatment by utilizing graphene oxide-catalyzed ozone

    CN105399195A

  • Preparation method and application of heterogeneous Fenton catalyst

    CN115282977A

  • Method and device for treating organic substance-containing waste solution

    JP2007090232A

  • Modified perovskite type composite oxide, method for preparing the same, and composite dielectric material

    US20110183834A1

  • Heterogeneous catalytic material, preparation method therefor, and use thereof

    WO2024192677A1